From Hombo Batu to the Realm of Physics: Implementation of Ethnophysics-Based Mobile Learning to Increase Learning Independence and Learning Outcomes - Dwi Saputra, M. Reza; Niethammer, Manuela; Adi Putra, Hangga Novian (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This study examines the effectiveness of Ethnophysics-based mobile learning (Hombo Batu) in enhancing students' learning independence and outcomes. This research is quantitative, employing a pretest-posttest control group design. The research sample consists of 23 students from class XIc as the control group, who received instruction using PowerPoint media, and 23 students from class XId as the experimental group, who received instruction using Ethno-Based Mobile Learning media. The study was conducted at Xin Zhong High School in Surabaya. The research instruments include learning outcome tests (pretest and posttest) and non-test instruments (learning independence questionnaires). The data analysis includes N-Gain analysis and Hotelling's Trace Multivariate Test (MANOVA). The results of the study indicate that learning with Ethno-Based Mobile Learning is more effective in enhancing learning independence compared to learning using PowerPoint, with an N-Gain value of 0.74 for learning independence and 0.79 for learning outcomes, as well as Hotelling's Trace results with a significance value of 0.00 (Ha accepted). The implication of using Ethno-Based Mobile Learning as a learning medium is that it can be utilized by Physics teachers to enhance students' learning independence and learning outcomes.